Ethnic Unemployment Rates and Frictional Markets - Laurent Gobillon; Peter Rupert; Etienne Wasmer (Institute for the Study of Labor (IZA), 2013)
The unemployment rate in France is roughly 6 percentage points higher for African immigrants than for natives. In the US the unemployment rate is approximately 9 percentage points higher for blacks than for whites. Commute time data indicates that minorities face longer commute times to work, potentially reflecting more difficult access to jobs. In this paper we investigate the impact of spatial mismatch on the unemployment rate of ethnic groups using the matching model proposed by Rupert and Wasmer (2012). We find that spatial factors explain between 1 to 1.5 percentage points of the unemployment rate gap in both France and the US, amounting to 17% to 25% of the relative gap in France and about 10% in the US. Among these factors, differences in commuting distance plays the most important role. In France, though, longer commuting distances may be mitigated by higher mobility in the housing market for African workers. Overall, we still conclude that labor market factors remain the main explanation for the higher unemployment rate of Africans.
Keywords: J15; J61; R23; 330; spatial mismatch hypotheses; commuting; job acceptance; ethnic unemployment rates; Arbeitslosigkeit; Schwarze; Ethnische Gruppe; Pendelverkehr; Kosten; Regionaler Arbeitsmarkt; Frankreich; USA